MIDDLE JURASSIC FLORA FROM THE HOJEDK FORMATION OF TABAS, CENTRAL EAST IRAN: BIOSTRATIGRAPHY AND PALAEOCLIMATE IMPLICATIONS (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2018)
The Middle Jurassic deposits of the Shemshak Group and Hojedk Formation are widespread in North, Central, and Central East Iran. In this paper, the Hojedk Formation in South Kouchekali, southwestern Tabas city, east-central Iran was studied for palaeobotany and stratigraphy. This formation contains well preserved plant macrofossils belonging to 43 species assigned to 24 genera of various orders such as Equisetales, Filicales, Bennettitales, Cycadales, Caytoniales, Ginkgoales and Pinales. One biozone and four subzones are recognized. The lower and the upper boundaries of this assemblage biozone are identified by the first and the last observed occurrences of Coniopteris hymenophylloides (Brongniart) Seward 1900 and Klukia exilis (Phillips) Raciborski 1890, respectively. According to the occurrences of these index species and Ptilophyllum harrisianum Kilpper 1968 and Nilssonia macrophylla Jacob & Shukla 1955, an early Middle Jurassic (Aalenian-Bajocian) age is considered for this assemblage biozone. Moreover, a comparative biostratigraphy for the Middle Jurassic of Iran is suggested. As a result, the Coniopteris hymenophylloides-Klukia exilis Assemblage biozone is proposed as a biozone widespread through the whole Iranian Plate. On the basis of the relative abundance of Filicales, Pinales, Cycadales, and Equisetales and of the high diversity and abundance of macrophyllous cycadophytes (eight species), a humid sub-tropical climate is suggested for this locality. In addition, floral gradient, correspondence analysis and similarity index were considered. Therefore, it is confirmed that a uniform palaeoclimate and vegetation cover occurred in Iran during the Middle Jurassic and that Iran was located within Vakhrameev's Euro-Sinian Region.